Congenital skin tumors of the newborn. Clinical features. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
We review the clinical aspects – diagnosis, prognosis, therapy – of neonatal congenital skin cancers, in particular of angiomas – infantile hemangioma, congenital hemangioma, “tufted” angioma, kaposiforme hemangioendothelioma, targetoid hemosiderotic hemangioma –, of mastocytosis, histiocytosis – juvenile xanthogranuloma and Langerhans cell histiocytosis –, fibromatous tumors – myofibroma and dermatofibrosarcoma protuberans –, neuroectodermal tumors – plexiform neurofibroma, benign and malignant proliferations on congenital melanocytic nevi –, and other malignancies – leukemia, rhabdomyosarcoma, neuroblastoma –.